Anti-Inflammatory and Antimicrobial Volatile Oils: Fennel and Cumin Inhibit Neutrophilic Inflammation via Regulating Calcium and MAPKs - Korinek, Michal; Handoussa, Heba; Tsai, Yi-Hong; Chen, You-Ying; Chen, Meng-Hua; Chiou, Zan-Wei; Fang, Yu; Chang, Fang-Rong; Yen, Chia-Hung; Hsieh, Chung-Fan; Chen, Bing-Hung; El-Shazly, Mohamed; et al. (Frontiers in Pharmacology, 2021)
Neutrophilic inflammatory diseases such as chronic obstructive pulmonary disease (COPD), acute respiratory distress syndrome (ARDS), or psoriasis exert a huge burden on the global health system due to the lack of safe and effective treatments. Volatile oils from terrestrial plants showed impressive therapeutic effects against disorders of the skin, digestive system, lungs, liver, metabolism, and nervous system. However, their effect on the immune system and neutrophils’ function is still elusive. Fennel, cumin, marjoram, lavender, caraway, anise are common nutraceuticals that are widely used in the Mediterranean diet. The volatile oils of these herbs were screened for various biological activities including anti-inflammatory, antiallergic, antimicrobial, and antiviral effects. Several oils showed anti-inflammatory and antimicrobial potential. Fennel (Foeniculum vulgare) and cumin (Cuminum cyminum) fruits volatile oils significantly suppressed the activation of human neutrophils including respiratory burst and the degranulation induced by a formyl peptide receptor agonists fMLF/CB and MMK1 in human neutrophils (IC50 3.8 to 17.2 µg/mL). The cytotoxic effect and free-radical scavenging effects (ABTS, DPPH) of these oils did not account for the observed effects. Both fennel and cumin volatile oils significantly shortened calcium influx recovery time and inhibited phosphorylation of MAPK (p38, JNK, and ERK) expression. The GC-MS analysis of these oils revealed the presence of estragole and cuminaldehyde as the major components of fennel and cumin volatile oils, respectively. Our findings suggested that cumin and fennel common in the Mediterranean diet hold the potential to be applied for the treatment of neutrophilic inflammatory diseases.